(3OQGSI GdLOhi hJbjje GdeTQhYGJ (B/s - (3YHO GdcQje, YHO GdYRjR eUWais ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2002)
(3CSGSjGJ GdeTQhY GdGbJUGOj(B-(3GdYhGFO hGdJcGdja ddeTQhY GdGbJUGOj(B-(3eQGMd Jbjje hJfajP GdeTQhYGJ GdGbJUGOjI(B-(3eYGjjQ Jbjje GdeTQhYGJ GdGbJUGOjI(B-(3GdeNGWQI hYOe GdJCcO hJbjje GdeTQhYGJs
(3GdedGMb U(B.259 (3HHdjhZQGajG(B: (3U(B.297-304s
Keywords: (3GdJNWjW GdEbJUGOjs; (3GdeTQhYGJs; (3OQGSI GdLOhis